Introducing the background of hungarian import in the highlight of the last decade - Pócsik, Orsolya (Studia Mundi – Economica, 2019)
Hungary is an open economy, that the country has need significant import and export. The Hungarian foreign trade is typically half-peripheral, it is defined by the relationship with EU Member States and V4 countries. In my study, I have tried to reveal tendencies of the recent years and I would like to draw conclusions and from the conclusions are examined by information and foreign trade data. In my paper, the author hasundertaken to realistic spectacle of the economic policy at the past decade, the challenges of foreign trade and foreign affairs nowadays, and to the situation of Hungarian import activities.